Age-dependent salt hypertension in Dahl rats: fifty years of research - Zicha, J; Dobešová, Z; Vokurková, M; Rauchová, H; Hojná, S; Kadlecová, M; Behuliak, M; Vaněčková, I; Kuneš, J (Physiological research, 2012)
Fifty years ago, Lewis K. Dahl has presented a new model of salt hypertension - salt-sensitive and salt-resistant Dahl rats. Twenty years later, John P. Rapp has published the first and so far the only comprehensive review on this rat model covering numerous aspects of pathophysiology and genetics of salt hypertension. When we summarized 25 years of our own research on Dahl/Rapp rats, we have realized the need to outline principal abnormalities of this model, to show their interactions at different levels of the organism and to highlight the ontogenetic aspects of salt hypertension development. Our attention was focused on some cellular aspects (cell membrane function, ion transport, cell calcium handling), intra- and extrarenal factors affecting renal function and/or renal injury, local and systemic effects of renin-angiotensin-aldosterone system, endothelial and smooth muscle changes responsible for abnormal vascular contraction or relaxation, altered balance between various vasoconstrictor and vasodilator systems in blood pressure maintenance as well as on the central nervous and peripheral mechanisms involved in the regulation of circulatory homeostasis. We also searched for the age-dependent impact of environmental and pharmacological interventions, which modify the development of high blood pressure and/or organ damage, if they influence the salt-sensitive organism in particular critical periods of development (developmental windows). Thus, severe self-sustaining salt hypertension in young Dahl rats is characterized by pronounced dysbalance between augmented sympathetic hyperactivity and relative nitric oxide deficiency, attenuated baroreflex as well as by a major increase of residual blood pressure indicating profound remodeling of resistance vessels. Salt hypertension development in young but not in adult Dahl rats can be attenuated by preventive increase of potassium or calcium intake. On the contrary, moderate salt hypertension in adult Dahl rats is attenuated by superoxide scavenging or endothelin-A receptor blockade which do not affect salt hypertension development in young animals.
Keywords: Animals; draslík; hypertenze; Sodium Chloride, Dietary; Age Factors; kuchyňská sůl; Potassium; věkové faktory; renin-angiotensin systém; Renin-Angiotensin System; vápník; Hypertension; Calcium; potkani inbrední Dahl; krysa rodu Rattus; Arterial Pressure; zvířata; Rats, Inbred Dahl; arteriální tlak; Rats